Cold-set gelation of whey protein isolate and low-methoxyl pectin at low pH. (April 2017) - Wijaya, Wahyu; Van der Meeren, Paul; Patel, Ashok R.
Abstract: We report the fabrication of homogenous aqueous gels formed by a heat-cool step of whey protein isolate (WPI) and low methoxyl pectin (LMP) mixtures at low pH (2.0). The low pH suppresses the electrostatic repulsion between LMP molecules, leading to stronger intermolecular interactions between WPI and LMP molecules. Response surface methodology was applied to optimize and to investigate the effects of WPI and LMP concentrations on the gelation temperature (Tsol-gel ), melting temperature (Tgel-sol ), storage modulus (G′), critical stress (σ*), and dynamic yield stress (σy ) of the gels. The obtained results revealed that most of the characteristics evaluated were affected by the process variables, while there was also a significant interaction effect of WPI and LMP concentrations on the gel storage modulus as the main indicator of gel formation. A higher concentration of WPI and LMP resulted in a gel with lower porosity and almost frequency independent moduli. The gel microstructure showed the role of WPI to stabilize and develop the pectin network as crosslinking agent. The WPI-LMP gels showed pH-responsive behavior at higher pH values and stability over a wide range of pH values depending on the total biopolymer concentrations studied, respectively, which can make them very attractive for applications in bio-related fields. Graphical abstract: Highlights: Synergistic gelation of WPI-LMP mixtures at low pH (through a heat-cool step). Cryo-SEM studies to understand the microstructure of synergistic gels. Use of RSM to tune the gel properties with WPI:LMP concentrations and ratios. Synergistic gels showed pH-responsive behavior and stability within a wide pH-range.